Pengaruh Sumber Daya Manusia terhadap Kinerja Karyawan : (Studi Kasus Bank Bjb Cabang Cibinong) - Aminati Zahra; Indupurnahayu Indupurnahayu (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The purpose of this study is to ascertain how the Human Resource Management Review affects employee performance at the Bank Bjb branch in Cibinong, specifically at PT. This research is a survey of cooperative causality. The 175 participants in this study were selected using the Solvin sampling approach. Based on the computation results, 70 respondents were chosen as the main survey population, using a 10% error threshold. The distribution of survey forms provided the study's main source of data. Prior to completing the field research, the instrument was put through a battery of testing including normality and heteroscedasticity tests, multiple regression analysis, t-test, f-test, and validity and reliability tests on seventy employees of PT Bank Bjb Cibinong Branch. The study's findings indicate a noteworthy and favorable distinction between the HR department Review and the work output of the PT Bank Bjb Cibinong Branch employees. An f-test was used to acquire these results, which were about 0.0000 < 0.05 and f count 18.121 > f table 2.47.